2009
DOI: 10.1177/1049731509331925
|View full text |Cite
|
Sign up to set email alerts
|

Iowa Case Management for Rural Drug Abuse

Abstract: Objective The purpose of this research was to evaluate the effectiveness of a comprehensive, strengths-based model of case management for clients in drug abuse treatment. Method 503 volunteers from residential or intensive outpatient treatment were randomly assigned to one of three conditions of Iowa Case Management (ICM) plus treatment as usual (TAU), or to a fourth condition of TAU only. All were assessed at intake and followed at 3, 6, and 12 months. Results Clients in all four conditions significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Core characteristics of included trials and studies are outlined in Table 1 and are briefly described below. Sixteen of the 21 clinical trials resulted in one study/publication, four trials were published as two publications (40, 41, 51, 5659, 65) and (55, 56) and one trial was reported in six studies/publications (4247). Case management was most frequently compared with existing referral procedures (11 trials).…”
Section: Resultsmentioning
confidence: 99%
“…Core characteristics of included trials and studies are outlined in Table 1 and are briefly described below. Sixteen of the 21 clinical trials resulted in one study/publication, four trials were published as two publications (40, 41, 51, 5659, 65) and (55, 56) and one trial was reported in six studies/publications (4247). Case management was most frequently compared with existing referral procedures (11 trials).…”
Section: Resultsmentioning
confidence: 99%
“…The mention of manuals for the interventions ranked second (62.5%) in the reviewed articles; however, 50% of them stated they actually used the manual in training, supervision, or throughout intervention's implementation. These articles explicitly indicated that the intervention is both manualized and the manual is being used during interventions by practitioners in order to minimize personal styles to affect results (e.g., see Hall et al, 2009;Kayser, Feldman, Borstelmann, & Daniels, 2010;Striley, Nattala, Abdallah, Dennis, & Cottler, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…As indicated in the literature, in order to ensure adherence to treatment fidelity accurately, it is critical to provide both training and supervision. The extent to which training and supervision was offered varied considerably, as few authors mentioned detailed context, hours, and times of training and supervision (e.g., see Hall et al, 2009). A ''description of the methods used'' to monitor the delivery and progress of treatment was reported in 50% of these articles.…”
Section: Discussionmentioning
confidence: 99%
“…Minimalist approaches involve brokerage interventions involving very limited supervision and referral. Brokerage models of case management attempt to match resources to client needs and are characterized by more office-based work, telephone contact, and larger caseloads; whereas comprehensive approaches are characterized by intensive service provision, outreach and direct involvement in counseling, skill development, family consultation and support, and crisis intervention (Hall et al, 2002(Hall et al, , 2009Lukersmith et al, 2016). In post-disaster settings, while people have no access to regular services to meet their various needs, and local organizations need time to restart their services, a comprehensive case management model could be useful because, as well as matching resources to client needs, social workers are committed to deliver direct and/or outreach services.…”
Section: Social Work Post-disaster Interventions In Poldokhtar Lorestanmentioning
confidence: 99%